Advancements in piezoelectric wind energy harvesting: A review - Ahsan Ali; Shaukat Ali; Hamna Shaukat; Eman Khalid; Laiba Behram; Habiba Rani; Wael A. Altabey; Sallam A. Kouritem; Mohammad Noori (Results in Engineering, 2024)
This paper highlights the advancement in wind energy harvesting using piezoelectric materials to produce sustainable power generation. It is a highly encouraging, fascinating, and challenging method to capture energy from piezoelectric materials. The purpose of this research is to evaluate the principal characteristic groups that affect energy harvesting performance and to provide recommendations for further improvement. Piezoelectric energy harvesters (PEH) can provide electricity for low-power electronic devices, which additionally possess the potential to boost self-powered, autonomous devices. The objective of this article is to provide recommendations for wind energy harvester modeling techniques. After establishing the fundamental idea of Piezoelectric Wind Energy Harvesters (PWEHs), it is next examined how well these devices function structurally and where their research stands in relation to various phenomena, including vortex-induced vibration, flutter, and galloping. A cantilever beam connected with a tip body is the typical component of a galloping piezoelectric harvester for wind energy collection. Wind energy has been turned into mechanical vibrations and ultimately into electrical power via the flutter phenomena. Fluttering-based wind energy harvesters are a new technology that provides an effective replacement for conventional wind turbines. The future development trend for PWEHs has been anticipated. The most current developments in strategies and approaches for wind energy harvesting using piezoelectric materials are also discussed in this paper. First, this paper highlights various piezoelectric energy harvesting materials, then it shows various wind energy harvesters’ design. After that this paper displays various types of wind energy harvesters and their applications. Finally, it highlights some challenges, future development, and recommendations.